Flexible Work Systems and the Structure of Wages: Evidence from Matched Employer- Employee Data - Thomas K. Bauer; Stefan Bender (Institute for the Study of Labor (IZA), 2001)
A growing literature is concerned with the effects of flexible workplace systems or High Performance Work Organizations (HPWOs) on wages. This paper makes use of a new employer-employee-linked panel data set for Germany to examine the effects of adopting HPWOs on wages as well as on the wage structure within firms. The empirical results suggest that, depending on the particular practice, flexible workplace systems benefit employees through higher wages. HPWOs further increase within firm wage inequality through a relative increase in the wages at the upper parts of an establishment?s wage distribution.
Keywords: O3; J3; L2; 330; organizational change; wages; linked-employer-employee data set; within-firm inequality; Arbeitsorganisation; Lohnstruktur; Arbeitsmarktsegmentierung; Deutschland